Some considerations on the 18th-century Russian-French cultural dialogue - Kazimierczyk-Kuncer, Jolanta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The paper presents an outline of the history of Russian and French cultural alliance, beginning with episodic contacts in the 16th and 17th centuries until the 18th c., which commences a dialogue with France that would continue over several hundreds of years. Its ideological and cultural principles became the source of inspiring civilization transformations and the foundation of the pro-Western identity of the then still until recently Holy Russia, with Peter I, “the Revolutionary on the Throne”, as the initiator and promoter of a Western – French – civilization. The process of infiltration by the French culture advanced further thanks to the fascination on the part of Peter I’s daughter Elizabeth with anything that was “in the French spirit”. This resulted in the phenomenon of Gallomania, which culminated in the second half of the 18th c., i.e. during the reign of Catherine II. At that time, with the Russian admiration for the French Enlightenment ideals in the background and thanks to Catherine II’s friendship with the Encyclopédistes (mostly Voltaire and Diderot), Russia – with its Enlightened Absolutism – aspired to the circle of the most powerful European countries.